2019
DOI: 10.20517/2572-8180.2019.05
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived vesicles: diagnostic and predictive value in cardiovascular diseases

Abstract: There is emerging evidence that endogenous microvesicles released by platelets may play a pivotal role in pathogenesis of numerous diseases including stable and unstable ischemic heart disease, atherosclerosis, hypertension, idiopathic pulmonary hypertension, atrial fibrillation/flutter, acute and chronic heart failure, as well as systemic vasculitis, systemic lupus erythematosus, antiphospholipid syndrome, transplant rejection, diabetes-induced angiopathy. Microvesicles that leased from the platelets exist as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 104 publications
0
9
0
Order By: Relevance
“…Previous clinical studies have shown that there were no significant differences in the circulating number of EVs derived from platelets (CD41a+), neutrophils (CD66b+), erythrocytes (CD235a+), monocytes (CD14+), T lymphocytes (CD3+), and B lymphocytes (CD19+) between healthy volunteers and HF patients (56). In contrast, a decreased number of circulating endothelial cells (CD31+CD41a-) EVs was found in HF patients (57). However, the total number of EVs enriched phosphatidylserines was significantly increased in HF patients compared with healthy volunteers (56).…”
Section: Circulating Blood Cells-derived Evsmentioning
confidence: 87%
“…Previous clinical studies have shown that there were no significant differences in the circulating number of EVs derived from platelets (CD41a+), neutrophils (CD66b+), erythrocytes (CD235a+), monocytes (CD14+), T lymphocytes (CD3+), and B lymphocytes (CD19+) between healthy volunteers and HF patients (56). In contrast, a decreased number of circulating endothelial cells (CD31+CD41a-) EVs was found in HF patients (57). However, the total number of EVs enriched phosphatidylserines was significantly increased in HF patients compared with healthy volunteers (56).…”
Section: Circulating Blood Cells-derived Evsmentioning
confidence: 87%
“…Platelet participation in several pathophysiological mechanisms involved in atherosclerosis, bypass stenosis, and restenosis is an important subject of research in human and experimental pathology [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Platelets act in angiogenesis [ 15 , 16 , 17 , 18 ], which is one of the main pathophysiological mechanisms of this pathology.…”
Section: Introductionmentioning
confidence: 99%
“…As already pointed out by Berezin et al and Gasecka et al, platelets are the main source of extracellular vesicles in plasma, which are the cargo for a large number of biologicalactive molecules including cytokines, chemokines, hormones, enzymes, growth factors, and their receptors (e.g., VEGF), as well as adhesion receptors coordinating cell-tocell interactions [50,51]. ey contribute to numerous biological mechanisms such as microvascular inflammation, atherosclerotic plaque shaping and rupture, endothelial dysfunction, angiogenesis, neovascularization, thrombosis, cardiac remodeling, and kidney dysfunction [52][53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 98%